Anti-neuroinflammatory effects of a food-grade phenolic-enriched maple syrup extract in a mouse model of Alzheimer's disease. (2nd September 2021) - Rose, Kenneth N.; Barlock, Benjamin J.; DaSilva, Nicholas A.; Johnson, Shelby L.; Liu, Chang; Ma, Hang; Nelson, Robert; Akhlaghi, Fatemeh; Seeram, Navindra P.
ABSTRACT: Objectives: Alzheimer's disease (AD) is a growing global health crisis exacerbated by increasing life span and an aging demographic. Convergent lines of evidence, including genome-wide association studies, strongly implicate neuroinflammation in the pathogenesis of AD. Several dietary agents, including phenolic-rich foods, show promise for the prevention and/or management of AD, which in large part, has been attributed to their anti-inflammatory effects. We previously reported that a food-grade phenolic-enriched maple syrup extract (MSX) inhibited neuroinflammation in vitro but whether these effects are translatable in vivo remain unknown. Herein, we assessed MSX's ability to attenuate early neuroinflammation in a transgenic mouse model of AD. Methods: The effects of MSX on AD-related neuroinflammation was evaluated by orally administering MSX (100 and 200 mg/kg/day for 30 days) to the 3xTg-AD mouse model of AD. The expression of inflammatory markers in mouse brains were analyzed with LC-MS/MS with SWATH acquisition. Results: 3xTg-AD mice dosed orally with MSX have decreased expression of several inflammatory proteins, including, most notably, the AD risk-associated protein 'triggering receptor expressed on myeloid cells-2' (TREM2), and stimulator of interferon genes TMEM173, and suppressor of cytokine signaling-6 (SOCS6). However, this decrease in inflammation did not coincide with a decrease in pathogenic amyloid generation or lipid peroxidation. Discussion: These data demonstrate that oral administration of this maple syrup derived natural product reduces key neuroinflammatory indices of AD in the 3xTg-AD model of AD. Therefore, further studies to investigate MSX's potential as a dietary intervention strategy for AD prevention and/or management are warranted.